(untitled) (Journal of Universal Science Research, 2023)
Artificial Intelligence (AI) has the potential to revolutionize education by enhancing the learning experience for students and supporting teachers in their instructional practices. By leveraging AI methods such as intelligent tutoring systems, virtual assistants, and data analytics, classrooms can become more personalized, engaging, and efficient. Students benefit from personalized learning pathways, adaptive feedback, and collaborative opportunities, leading to improved comprehension, critical thinking skills, and self-directed learning. Teachers, on the other hand, can automate administrative tasks, gain data-driven insights into student performance, and implement personalized instructional strategies. The integration of AI in education holds the promise of improved learning outcomes, increased efficiency, and a transformative educational experience for all stakeholders.